2008
DOI: 10.1021/bi800060w
|View full text |Cite
|
Sign up to set email alerts
|

Cell Free Expression and Functional Reconstitution of Eukaryotic Drug Transporters

Abstract: Polyspecific organic cation and anion transporters of the SLC22 protein family are critically involved in absorption and excretion of drugs. To elucidate transport mechanisms, functional and biophysical characterization of purified transporters is required and tertiary structures must be determined. Here, we synthesized rat organic cation transporters OCT1 and OCT2 and rat organic anion transporter OAT1 in a cell free system in the absence of detergent. We solubilized the precipitates with 2% 1-myristoyl-2-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
56
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 51 publications
2
56
0
Order By: Relevance
“…To make this assumption a priority is not justified since evidence has been provided that OATs and OCTs form homo-oligomers. Hong and co-workers (11) showed that human OAT1 (hOAT1) forms oligomers in cultured cells and kidney, and we provided evidence that rOat1, rOct1, and rOct2 form homo-oligomers in detergent solution (12). A recent study suggests that the sixth transmembrane ␣-helix (TMH) of hOAT1 comprises a contact region for oligomerization and that surface expression of hOAT1 was reduced when oligomerization of hOAT1 was disturbed (13).…”
mentioning
confidence: 71%
See 4 more Smart Citations
“…To make this assumption a priority is not justified since evidence has been provided that OATs and OCTs form homo-oligomers. Hong and co-workers (11) showed that human OAT1 (hOAT1) forms oligomers in cultured cells and kidney, and we provided evidence that rOat1, rOct1, and rOct2 form homo-oligomers in detergent solution (12). A recent study suggests that the sixth transmembrane ␣-helix (TMH) of hOAT1 comprises a contact region for oligomerization and that surface expression of hOAT1 was reduced when oligomerization of hOAT1 was disturbed (13).…”
mentioning
confidence: 71%
“…Cell-free Expression of Transport Proteins-Cell-free expression was performed in the continuous exchange mode using bacterial extracts from Escherichia coli strain A19 as described (12,19). Reaction mixture and feeding mixture were composed as described (19).…”
Section: Constructs For Transient Expression In Hek293 Cells For Fluomentioning
confidence: 99%
See 3 more Smart Citations